Pengaruh Penerapan Kebijakan Merdeka Belajar Di Perguruan Tinggi - Ilma Siti Salamah; Rifqi Taufiqul Hakim; Lahera, Tia (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Significant changes occurred in various industrial sectors, especially in the education sector, so that the government issued an independent learning policy to deal with the paradigm that occurred in the current era. This study aims to determine the effect of implementing an independent learning policy in universities, and to determine the positive and negative sides of the implementation of an independent learning policy on students and universities. The research method used is a literature study which produces descriptive data regarding the influence or impact of the implementation of the independent learning policy in higher education. The results showed that most of the students gave a positive response to the independent learning policy and had implemented various programs contained in this policy. However, in its implementation there is a negative side to students that needs to be minimized so that the implementation and implementation of this policy runs optimally.